(untitled) (Journal of the Bangladesh Agricultural University, 2014)
The present study was undertaken to examine the marketing channel, marketing margin, seasonal price variation, problems and probable solutions of egg marketing in Gazipur district. The sample size of the study was 55 which included 15 layer farm owners and 40 egg traders selected purposively. Data were collected from both primary and secondary sources. In egg marketing system five different channels were identified. The average marketing costs for layer farm owner, arathder, wholesaler, wholesaler cum retailer and retailer were Tk. 3.23, Tk. 20.60, Tk.16.34, Tk.13.09 and Tk. 12.51 per 100 eggs, respectively. The net marketing margins for arathder, wholesaler, wholesaler cum retailer and retailer were estimated at Tk. 9.40, Tk.13.60, Tk. 21.91 and Tk. 32.50. Price was the highest in the month of July and lowest in the month of December. There was a wide seasonal price variation of egg in the selected markets due to change in demand and supply at different times of the year. The study identified some problems of layer farming and marketing of egg, and suggested measures for solving these problems. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19926 J. Bangladesh Agril. Univ. 11(2): 277-284, 2013